Complete heart block in a neutropenic patient with invasive aspergillosis - (:unkn) unknown (My University, 2006)
A patient with leukemia who developed complete heart block after the diagnosis of pulmonary aspergillosis is reported. The patient had probable invasive pulmonary aspergillosis with a sudden tachypnea, dyspnea, fever, bilateral pulmonary infiltrates and acute respiratory insufficiency after chemotherapy. On the sixth day of antifungal therapy, she developed complete atrioventricular block. Complete heart block has not been reported during liposomal amphotericin B (LAMB) therapy. Local or hematogenous involvement of the myocardium with aspergillosis may be the most likely explanation of the complete heart block. © Turkish Society of Hematology.
Keywords: Complete heart block; Invasive pulmonary aspergillosis